PERAN DINAS PERPUSTAAKAN DAN KEARSIPAN PROVINSI KALIMANTAN BARAT DALAM PRESERVASI BUKU BAHASA DAERAH DI KALIMANTAN BARAT - Madeten, Sesiliya Saman; Kurniawan, Kurniawan (UPT Perpustakaan UIN Alauddin Makassar, 2026)
This study investigates the role of the West Kalimantan Provincial Library and Archives Office in preserving regional language collections to protect local cultural identity. Despite a steady increase in total annual deposit collections since 2008, regional language materials constitute only a very small fraction (0.07% to 0.26%) of total acquisitions. Through a qualitative descriptive approach involving interviews, document analysis, and observations with librarians, officials, and cultural actors, the study finds that preservation efforts are incidental rather than strategic. Key challenges include limited budgets, lack of technical expertise, restricted access to private collections, and absence of supportive policies. The study proposes a “Community-Based Deposit and Digital Preservation Model” that combines targeted deposit policies, community collaboration, and digital heritage strategies to enhance intergenerational transmission and sustainable preservation. This research positions regional libraries as proactive agents in digital cultural safeguarding, advancing the transformation of local libraries beyond mere repositories.